2016
DOI: 10.1123/japa.2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term High-Effort Endurance Exercise in Older Adults: Diminishing Returns for Cognitive and Brain Aging

Abstract: While there is evidence that age-related changes in cognitive performance and brain structure can be offset by increased exercise, little is known about the impact on these of long-term high-effort endurance exercise. In a cross-sectional design with 12-month follow-up, we recruited older adults engaging in high-effort endurance exercise over at least twenty years, and compared their cognitive performance and brain structure with a non-sedentary control group similar in age, sex, education, IQ, and lifestyle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Cross-sectional studies suggest that lifestyle factors such as physical activity (PA) and cardiorespiratory fitness (CRF) are protective against cognitive and neural decline. For example, we have shown that greater PA and CRF are associated with greater WM integrity (Burzynska et al, 2014; Oberlin et al, 2016) and that older aerobically trained athletes have greater brain structural integrity and cognitive performance than their sedentary low-fit peers (Tseng et al, 2013; Burzynska et al, 2015; Young et al, 2016). However, a recent meta-analysis showed only modest cross-sectional effects of CRF and aerobic PA on WM in aging (Sexton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies suggest that lifestyle factors such as physical activity (PA) and cardiorespiratory fitness (CRF) are protective against cognitive and neural decline. For example, we have shown that greater PA and CRF are associated with greater WM integrity (Burzynska et al, 2014; Oberlin et al, 2016) and that older aerobically trained athletes have greater brain structural integrity and cognitive performance than their sedentary low-fit peers (Tseng et al, 2013; Burzynska et al, 2015; Young et al, 2016). However, a recent meta-analysis showed only modest cross-sectional effects of CRF and aerobic PA on WM in aging (Sexton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Seniors who had a longer experience of physical activity showed better results, but no significant differences were found between physically active and inactive seniors and their cognitive and motor indicators. Also, no significant differences between physically active and inactive people were found in the study of other researchers in 2016 (Young, Dowell, Watt, Tabet, & Rusted, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…114 In contrast, 2 decades of high-effort endurance exercise reported by older adults documented no cognitive differences compared with a nonsedentary control group of similar age. 115 Some of the limitations of the prospective exercise trials may be better addressed when the independent variable is fitness, which is the intended outcome of aerobic exercise. Fitness can be physiologically defined by the measured oxygen uptake during maximum exercise.…”
Section: Results: Human Studies Humans and Neurotrophic Factorsmentioning
confidence: 99%